Optimizing Student Management In Instilling Good Morals In The Madrasah Environment - Mohamad Madum; Isnaini Isnaini (Insitut Muslim Cendekia, 2025)
This study aims to examine the role of student management in optimizing superior programs to instill moral values in MTs N 2 Purworejo. The method used in this study is field research with a qualitative approach, which is carried out directly in the MTs N 2 Purworejo environment. Data collection is carried out through interviews, observations, and documentation to ensure the accuracy of this. Data analysis applies the Miles and Huberman model, which includes the stages of data reduction, data presentation, and conclusions drawn. The results of the study show that the optimization of student management in forming moral character in MTs N 2 Purworejo has run effectively through four main stages: planning, organizing, implementing, and evaluating. The planning stage begins with a meeting at the beginning of the year, while the organizing stage includes the preparation of a schedule and the formulation of SOPs regarding adab. The implementation of the program involves all elements of the madrasah through various activities, such as 3S culture (Smile, Salutation, Greeting), joint prayer, tadarus, congregational prayers, as well as literacy and hygiene programs. Evaluations are carried out periodically through monthly meetings, and attitude assessments are included in student report cards. This research has implications for education practitioners in both formal and non-formal education.